Role of cardiac magnetic resonance imaging in assessing the risk of various myocardial remodeling types in left ventricular noncompaction: genetic analysis data - E. A. Mershina; D. A. Filatova; R. P. Myasnikov; O. V. Kulikova; A. N. Meshkov; A. V. Kiseleva; V. E. Sinitsyn; M. S. Kharlap (Кардиоваскулярная терапия и профилактика)
Aim. To analyze contrast-enhanced cardiac magnetic resonance imaging (MRI) in patients with phenotypic manifestations of left ventricular non-compaction (LVNC) and related genetic mutations, as well as to determine the relationship between mutations and types of left ventricular (LV) remodeling and with a number of other morphological and functional cardiac parameters.Material and methods. From the registry of patients with LVNC and their relatives, patients with morphological signs of LVNC and 4 related mutations (MYH7, MYBPC3, TTN, and desmin genes (DES, DSG2, DSP and DSC2)). All patients underwent contrast-enhanced cardiac MRI, based on which the type of LV remodeling was determined.Results. The study included 44 patients who, according to genetic analysis, had mutations in sarcomeric genes responsible for LVNC development. In each patient, the type of LV remodeling was determined based on cardiac MRI results. We found that if patients with LVNC have mutations in the MYBPC3 and TTN genes, the chance of LV dilatation remodeling is significantly higher. On the contrary, in the presence of a DES gene mutation, the probability of this LV remodeling is lower, and milder morphological manifestations of LVNC are noted.Conclusion. The combination of cardiac MRI data and genetic analysis improves the morphological and functional stratification of patients with LVNC.